PENGARUH METODE DRILL TERHADAP PENINGKATAN KEMAMPUAN MAHASISWA PADA MATA KULIAH STATISTIK - Yoko Masna Rivan M; Febria Rahmi; Yeffi Masnarivan (STKIP Pesisir Selatan, 2018)
Carry out or manage learning about statistics is required is the liveliness of the teachers (educators) in creating and fostering activities of students (learners) learning in accordance with the plans that have been drawn up in planning (Sudjana, 2013). This research aims to know the influence of the drill method against an increase in the ability of students in the course statistics in Prima STIKes Nusantara Bukittinggi year 2018. This type of research is research experiments with design wants a Pre (Pre-Experimental Design) and design that is One Group Pre Test Post Test. Population in this study are all students Nusantara STIKes Prima registered in 2017-2018 teaching that takes eyes College statistics. The sample in this study i.e., the entire population was made a subject of research i.e. 55 students. Univariate analysis showed that the average value of Pre Test amounted to 60.82 and average value of Post Test of 78.76. Whereas, bivariat use test t-Test Dependent. Obtained results that the drill method to increase the ability of students in the course statistics in Prima STIKes Nusantara Bukittinggi year 2018 with p < 0.05 (0.0001). Therefore, it is recommended to educational institutions so that it can use this drill method can be applied in the process of learning as one of the effective methods for statistics courses